Bahasa Inggris - Sarwo Edi; Ahmad Fariz Malvi Zamzam Zein; Witri Pratiwi (Medika Kartika : Jurnal Kedokteran dan Kesehatan, 2026)
Type 2 diabetes mellitus is a major global health concern with increasing prevalence rates and is often accompanied by gastroparesis, a disorder that affects gastric motility and negatively impacts diabetes control. This study aimed to determine the prevalence and severity of gastroparesis symptoms among patients with type 2 diabetes mellitus in the area served by Waled Cirebon General Hospital. This cross-sectional observational study recruited 96 patients with type 2 diabetes mellitus who met the selection criteria between May and June 2025. Gastroparesis symptoms were assessed using the validated Gastroparesis Cardinal Symptom Index questionnaire . Data were collected through structured interviews and review of existing medical records. Statistical analyses included univariate descriptive statistics and bivariate analyses using Spearman’s correlation test and the Chi-square test, with statistical significance set at p < 0.05. The severity of gastroparesis symptoms was classified as severe in 43.8% of participants, moderate in 24.0%, and mild in 32.3%. The results revealed that significant associations existed between the severity of gastroparesis symptoms and age (r = 0.354, p = 0.001), gender (p < 0.001), duration of diabetes (r = 0.535, p = 0.001), blood glucose control, (r = 0.379, p = 0.001), smoking (r = 0.636, p = 0.001), and body mass index. The prevalence of severe gastroparesis symptoms in this population exceeded reported global rates. All identified risk factors were signicantly associated with symptom severity, with obesity and smoking showing the strongest association. This study highlights the importance of optimal diabetes control involving several modifiable risk factors, proper screening for gastroparesis, and appropriate intervention among the high-risk population. Keywords: body mass index, diabetes mellitus type 2, gastroparesis, prevalence, risk factors DOI 10.35990/mk.v9n2.p160-172